Fatigue assessment of Ti-45Al-2Mn-2NbXD sub-element specimens. (January 2017) - Li, Yong; Dixon, M.; Ortiz, J.; Bache, M.R.
Abstract: A novel test technique is described for the sub-element fatigue assessment of dovetail geometric features commonly employed as a fixture for blade/disc assemblies in steam and gas turbines. Once developed, the test method was employed to assess the performance of a model dovetail geometry employing the gamma titanium aluminide Ti-45Al-2Mn-2Nb XD . In addition to generating information describing fatigue crack initiation, crack growth and ultimate failure, essentially via a trans-lamellar failure process, the associated wear processes were also characterised. Highlights: A novel test technique has been designed to assess wear and fatigue characteristics of model TiAl aerofoil dovetail root fixtures. The wear damage and the fatigue strength on cast γ -TiAl dovetail lobs has been investigate. A finite element stress model successfully predicted the highest stress location at the contact bedding area.